PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP PENGEMBANGAN KARIR SERTA DAMPAKNYA TERHADAP KINERJA KARYAWAN LEMBAGA LAYANAN PEMASARAN KOPERASI DAN USAHA KECIL DAN MENENGAH (LLP-KUKM) - Sigit, Suprianto; Efendi, Sugito; Sugiono, Edi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
This study aims to analyze and prove the direct influence of leadership style, organizationalculture and work discipline on the performance of LLP-KUKM employees, the directinfluence on career development, and the direct influence of career development on theperformance of LLP-KUKM employees, as well as the indirect effect of style. leadership,organizational culture and work discipline on the performance of LLP-KUKM employeesthrough career development. In this study, there was evidence that leadership style and workdiscipline directly had a positive and significant effect on the performance of LLP-KUKMemployees, and had a positive and significant effect on career development, whileorganizational culture had a direct positive and significant effect on the performance ofLLP-KUKM employees but did not. effect on career development. Leadership style, and workdiscipline indirectly have a positive and significant effect on the performance of LLP-KUKMemployees through career development, while organizational culture does not indirectlyaffect the performance of LLP-KUKM employees through career development.